Peran Sekolah dalam Mengintegrasikan Pengajaran Toleransi Beragama di Wilayah Multietnis - Muflih Nurriza Pahlawi; Muh. Hanif (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2025)
Inter-religious conflicts remain prevalent in Indonesia, with a notable increase in active intolerance among youth from 2016 to 2023. These tensions highlight the urgent need to cultivate religious tolerance as a foundation for fostering a harmonious, peaceful, and inclusive society. This study aims to analyze the role of SMP Negeri 1 Sumpiuh in promoting tolerance among its students. Employing a descriptive qualitative method, data were collected through observations and interviews with nine informants. Observations focused on student interactions within the school environment, while interviews explored perspectives related to the cultivation of tolerance. Data analysis involved four stages: data collection, data condensation, data presentation, and conclusion drawing. The findings indicate that the school plays a significant role in embedding religious tolerance through the leadership of the principal, the role of teachers, applied learning methods, and the availability of supportive school facilities. The principal plays a key role in fostering a tolerant and harmonious school climate. Teachers serve as role models, implementers of tolerance-based character education, and act as surrogate parents within the school setting. The development of students' tolerance is primarily achieved through habitual practices and exemplary behavior. Additionally, facilities that support religious activities and structured routines contribute to a conducive and inclusive learning environment.